Prison Inmates Living with HIV in India: Case Studies from Prisons in Maharashtra - Guin, Sayantani (Springer, 2015)
This Brief presents preliminary findings from research in three prisons in Maharashtra, India on experiences of prison inmates there living with HIV. The study explores health care services in these prisons, and problems experienced by inmates in India living with HIV, as well as their staff and caregivers. Through this preliminary study, the researchers shed light on the experiences of inmates in Indian prisons, with an aim of presenting questions for future research. The author provides an overview of the global conditions of prison inmates living with HIV, as an international comparative context for examining the cases in India. Major problems highlighted in the cases include: living conditions, high risk behavior during incarceration, delivery of medical services and adherence to ethical guidelines. Results of the study reveal that overcrowding and inadequate nutrition were major concerns for inmates living with HIV; there were no support systems available inside the prisons to address the stress related issues of the inmates; and, the prison hospital did not have provisions to cater to the treatment needs of inmates living with AIDS. The study also found that confidentiality regarding the HIV positive status could not be maintained inside the prison. This Brief presents a window into the experience of inmates in India, and presents questions for future research to understand and improve living conditions and medical service delivery within the prison system. This work will be of interest to researchers in criminology and criminal justice, particularly interested in incarceration or health issues, public health and related areas such as public policy, international studies, and demography studies in India.